(untitled) (Revista Contexto & Educação, 2026)
For implementing an education that highlights issues such as sustainability, climate change, ethics, and sociocultural diversity, among other related topics, two main points stand out: the development of sustainability skills and the use of teaching methodologies and strategies that foster these skills. Thus, the present work proposes to evaluate the main methodologies and strategies used for education for sustainability (EfS) in the training of engineers through a literature review. The methodology adopted for selecting the articles to be analyzed was the Methodi Ordinatio, composed of nine main stages. The keywords used were "engineering education" and "sustainability," which were searched in the Scopus, Science Direct, and Web of Science databases, with a time limit from January 2013 to March 2023. It was possible to classify 231 documents as studies that specifically discuss teaching methodologies and strategies, of which 38 were read in full for analysis. Fifteen different methodologies and strategies were mapped that suggest they are linked to learning theories with a cognitivist and humanistic approach, highlighting theorists and thinkers such as Lev Vygotsky, Jean Piaget, David Ausubel, Jerome Bruner, Gowin, Paulo Freire, and Carl Rogers. Thus, this study is a relevant synthesis of teaching methodologies and strategies, supported by learning theories, that can be applied in the educational context to foster education for sustainability in the training of future engineering professionals.